Integrated transcriptomic and metabolomic analysis reveals developmental stage-specific molecular responses to phosphorus deficiency in soybean - Liu, Xiulin; Wang, Xueyang; Zhang, Chunlei; Zhang, Fengyi; Zhao, Kezhen; Yuan, Rongqiang; Lamlom, Sobhi F.; Zhang, Bixian; Ren, Honglei (Frontiers in Plant Science, 2025)
Background and knowledge gapPhosphorus (P) deficiency is a major constraint to crop productivity worldwide, yet the molecular mechanisms behind stage-specific responses to severe P limitation during soybean development are not well understood. Although previous studies have looked at P stress responses, comprehensive multi-omics analyses across different developmental stages are missing, which limits our understanding of how P-efficient cultivars manage metabolic and transcriptional responses throughout their growth cycle.Objectives and methodsThis study used an integrated transcriptomic and metabolomic approach to analyze stage-specific responses to severe phosphorus limitation (99.875% reduction) in the P-efficient soybean cultivar Heinong 551 across four developmental stages: trefoil, flowering, podding, and post-podding.ResultsMetabolomic profiling identified 280 differentially expressed metabolites (DEMs) during trefoil and 851 during flowering, showing a threefold increase in metabolic disturbance during reproductive development. Transcriptomic analysis revealed 15,401 differentially expressed genes (DEGs) across stages, with 94% occurring in early phases (trefoil: 3,825; flowering: 10,660). Functional enrichment showed stage-specific responses, with the trefoil stage enriched in cell wall and membrane processes, and flowering enriched in photosynthesis, isoflavonoid biosynthesis, and cuticle development. Transcription factor analysis identified 87 differentially expressed transcription factors from 31 families, mainly bHLH, bZIP, and WRKY. Integrated multi-omics analysis under strict criteria (correlation coefficient |r| > 0.9) revealed networks between transcripts and metabolites, with flowering showing increased transcriptional control over metabolism. Key trade-offs included a shift from sucrose export to starch storage, suppression of nitrogen enzymes, and activation of antioxidant defenses despite oxidative damage. Physiological principal component analysis explained 92% of variance, distinguishing treatment groups and three metabolic clusters: carbon assimilation/export, nitrogen assimilation, and stress response.ConclusionCarbon metabolism exhibited compensatory mechanisms, including increased RubisCO and invertase activities, while nitrogen metabolism involved the downregulation of nitrate reductase, glutamine synthetase, and protein content. These findings reveal stage-specific molecular strategies used by P-efficient soybeans under severe limitation and inform sustainable agriculture practices aimed at optimizing crop performance in phosphorus-deficient conditions.